Answer:
a) 18
b)x^2+10x+18
c)x^2 -6x+2
Step-by-step explanation:
This is a case of plugging in the value into f(x).
a) f(-8)= -8^2 + 6(-8) +2
f(-8)= 64 + (-48) +2
f(-8)=64 + (-46)
f(-8)=18
b) f(x+2)= (x+2)^2+6(x+2)+2
So here I'll take a break to explain what's going on, because x+2 is a binomial meaning two terms and it is being squared I have to multiply the whole thing by itself. Meaning: (x+2) x (x+2), this is also known as foiling!! and for the next part its distributing 6 into x and 2.
f(x+2)= x^2+4x+4+6x+12+2
I'll reorder it
f(x+2)= x^2+4x+6x+12+2+4
f(x+2)= x^2+10x+18
c) f(-x)= -x^2+6(-x) +2
f(-x)= x^2 -6x+2
Answer:
ITS A
Step-by-step explanation:
PLZ GIVE BRAINLEIST
So 16=heads
18=tails
after you add some tails
18+x
ratio of heads to tails is 1:1.5
heads=16, didn't change
tails=18+x
so
1:1.5=16:18+x
fractionify
1/1.5=16/(18+x)
1/1.5=2/3
2/3=16/(18+x)
mutiply both sides by (3)(18+x)
2(18+x)=3(16)
36+2x=48
subtract 36 from both sides
2x=12
divide 2
x=6
6 tails added
total=heads+tails
heads=16
tails=18+6=24
total=16+24
total=40
6 tails added
40 total coins
Answer:
14a + 20
Step-by-step explanation:
8(a + 2) + 2(2 + 3a)
expand the bracket
8a + (8*2) + (2*2) + (2*3a)
8a + 16 + 4 + 6a
bring like terms together
8a + 6a + 16 + 4
14a + 20
Answer:
9: 89°
Step-by-step explanation:
Inside of a triangle is 180, so 180-39-52=89
I'm sorry I can't answer 10 for you